Sikap Posesif dan Kecerdasan Emosional dengan Pola Asuh Otoriter pada Mahasiswa dalam Membangun Relationship di UIN Raden Fatah Palembang - Rahma, Zanjabila; Uyun, Muhamad (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The first stage of development that distinguishes intimacy from isolation is described by the individual. In other words, at this point, the individual dewasa awal has an obligation to develop an intimate relationship with the type of lawan. This type of relasi is developed in a healthy way within a romantic or even a romantic relationship. This study uses a korelasional quantitative approach and is analyzed using a berganda regression. Using the purposive sampling technique, a sample of around 55 respondents was collected. The data was collected using three non-factual scales and distributed via a Google Form to UIN Raden Fatah Palembang mahasiswa with ages ranging from 18 to 25. Based on the simultaneous results, which are shown by the nilai F observasi = 147,205 > 3,18, there is a connection between the otoriter's pola asuh and the sikap posesif and kecerdasan emotional.